Comparison of Clinical, Metabolic, Hormonal, and Ultrasound Parameters among the Clomiphene Citrate-Resistant and Clomiphene Citrate-Sensitive Polycystic Ovary Syndrome Women - Sachdeva, Garima (J Hum Reprod Sci, 2019)
OBJECTIVE: The objective of the study is to compare the clinical, metabolic, hormonal, and ultrasound parameters among the clomiphene citrate (CC)-sensitive and CC-resistant polycystic ovary syndrome (PCOS) women. MATERIALS AND METHODS: This was a prospective observational study. SETTING: The study was conducted at the infertility outpatient department in a government hospital. SAMPLE SIZE: A total of 164 women with PCOS-related infertility were included. INTERVENTION: Incremental dose of CC from 50 mg/day to 100 mg/day to 150 mg/day over three cycles was given. RESPONSE: Ovulation was the outcome. Those who failed to ovulate with 150 mg CC were CC resistant. RESULTS: Of the total 164 PCOS women, 88 (53.7%) were CC resistant and 76 (46.3%) were CC sensitive. Of the 76 PCOS women who ovulated, maximum, i.e., 37 (22.6%) women ovulated with 100 mg CC. The most common diagnostic feature of PCOS in this study was hyperandrogenism (96.3%). CC-resistant PCOS women had significantly higher weight, waist circumference, waist-hip ratio, and body mass index (BMI). Significantly longer menstrual cycles and hyperandrogenism were significantly more common in CC-resistant group. CC-resistant group had a significantly higher ovarian reserve (ovarian volume, antral follicle count, and anti-Müllerian hormone values). Baseline luteinizing hormone (LH) values and LH-follicle stimulating hormone ratio were significantly higher in the CC-resistant group. CONCLUSION: Clomiphene-resistant PCOS women have significantly higher hyperandrogenism, longer cycles, more deranged metabolic profile, higher BMI, and ovarian reserve. These differences should be kept in mind while deciding the ovulation induction protocol.